¨Estudio ergonómico en el levantamiento de cargas u su incidencia en la zona lumbar en los operadores del área de abastecimiento de la empresa Sedemi scc.¨ - Bejarano Carlos, Cartagena Lema, Edgar William (2016)
La Compañía SEDEMI SCC (Servicio de Mecánica Industrial Sociedad Civil Comercial)., continually it is looking for new ways to improve the conditions of the working environment to forewarn the integrity of workers, for that it has been made ergonomic study based on the statistical data of medical department of the company , becoming the most influent the supply area where the main activity is heavy lifting and occupational diseases occur such as backache for which it was analyzed, evaluated ergonomic risks regarding lifting loads that cause lumbar diseases, in that way it is sought to reduce risks and prevent such diseases. For this study it has taken into account the NIOSH method, and the software of ergonautas of the University to assess the rate of rise of loads, where it is collected data of each worker task by task, and then to enter data into the software and to get results that can view the index of rising load and to analyze the incidence with lumbar diseases (backache) existing in the area. According to the results of the evaluation, almost most tasks the index is high, and it is justified the incidence of lumbar diseases in workers in the area, therefore it allows to present a proposal to minimize the rate of attention with respect to muscle aches, more than the recommendations that the software launches for each task. The backache prevention plan is presented, where the steps are detailed for handling a load, most of the staff did not have knowledge of how to perform a proper lifting load. The plan was socialized to all operational and administrative staff involved of the company. According to the statistical data of morbidity in reference first half of 2016 it was a significant difference in reducing number of patients with skeletal muscle disorders that supply area shows.